Correlation of Abstract Religious Thought and Formal Operations in High School and College Students - Zachry, William H. (Review of religious research, 1990)
The relationship between formal operational thinking and abstract religious thought was investigated in a sample of 70 high school and college students, ages 14-33 years. Scores on the Formal Operational Reasoning Test (Roberge & Flexer, 1982) were correlated with scores derived from a modification of Peatling's Thinking About the Bible Test (Peatling, 1973). The product-moment correlation of +.315, controlled for age, was significant at the .01 level. This result is consistent with the prediction of Piagetian theory that abstract thought in a specific content area such as religion depends on an underlying formal logic. Problems in measuring abstract religious thought in Biblical literalists are discussed.